Transitions of low educated graduates - Arjen Edzes; Marije Hamersma; Jouke Van Dijk (European Regional Science Association (ERSA), 2011)
This paper deals with the question of regional variation in two transitions that low educated can make. The first transition is the choice between learning through versus not learning and entering the labour market. Second, if they enter the labour market, the question is whether there is a regional difference in outcomes in terms of earned wages. Several explanatory regional circumstances are considered like urbanization and regional economic growth. The questions are analyzed using data of a schoolleaverssurvey in the period of 1996-2008 in the Netherlands.
Keywords: 330